Analgesic effect of benzathine penicillin - Mungen, B.; Akyol, A.; Kiziltan, G.; Kerman, M.; Bulut, S.; Baydas, B. (My University, 1996)
[Abstract Not Available]
Keywords: benzathine penicillin; adult; analgesic activity; clinical article; clinical trial; controlled clinical trial; controlled study; drug efficacy; female; human; intramuscular drug administration; letter; male; pain